2021
DOI: 10.1111/nph.17421
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility relates to fungal‐mediated decomposition and organic matter turnover in a temperate mountain forest

Abstract: Fungi are known to exert a significant influence over soil organic matter (SOM) turnover, however understanding of the effects of fungal community structure on SOM dynamics and its consequences for ecosystem fertility is fragmentary.Here we studied soil fungal guilds and SOM decomposition processes along a fertility gradient in a temperate mountain beech forest. High-throughput sequencing was used to investigate fungal communities. Carbon and nitrogen stocks, enzymatic activity and microbial respiration were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 84 publications
(244 reference statements)
1
32
0
Order By: Relevance
“…The nutrient-rich site in boreal Scots pine forests was reported to have a high amount of above-ground litter production (Starr et al 2005), which induced a thick organic layer. A faster turnover rate of SOM in a nutrient-rich site was reported to be closely related to soil fungal decomposition (Mayer et al 2021), confirming our assumption. Moreover, a defoliation experiment conducted in northern Finland reported that the defoliation increased the C limitation in colonized EcM mycelia by decreasing the EcM production and percentage of thick-mantled mycorrhizae of Betula pubescens seedlings (Markkola et al 2004).…”
Section: Ectomycorrhizal Mycelia Productionsupporting
confidence: 88%
“…The nutrient-rich site in boreal Scots pine forests was reported to have a high amount of above-ground litter production (Starr et al 2005), which induced a thick organic layer. A faster turnover rate of SOM in a nutrient-rich site was reported to be closely related to soil fungal decomposition (Mayer et al 2021), confirming our assumption. Moreover, a defoliation experiment conducted in northern Finland reported that the defoliation increased the C limitation in colonized EcM mycelia by decreasing the EcM production and percentage of thick-mantled mycorrhizae of Betula pubescens seedlings (Markkola et al 2004).…”
Section: Ectomycorrhizal Mycelia Productionsupporting
confidence: 88%
“…Thus, we propose that the abundance of ECM with peroxidases restricts SOM accumulation across gradients of soil inorganic N availability, but that the direction of this relationship depends on the location along a broader continuum of N availability and photosynthate allocation that connects boreal and temperate ecosystems (Figure 6). Exceptions to this pattern could occur where narrower ranges of soil N availability in fertile temperate forests cause less variation in ECM abundance (Mayer et al, 2021) or where dramatic transitions in boreal and subarctic ecosystem types reverse the relationships between environmental stress, host allocation to ECM with greater decay potential, and N availability (Clemmensen et al, 2021).…”
Section: Discussion Turnover In Ecm Composition Constrains Som Accumu...mentioning
confidence: 99%
“…In contrast, SOM stocks decline with increasing N availability in fertile boreal forests because of an increase in ligninolytic saprotrophic fungi (Kyaschenko et al, 2017), which also decay lignified compounds in plant litter and SOM using peroxidases (Floudas et al, 2012). In a high-fertility temperate forest, SOM declined with increasing N availability due to greater decay by non-ligninolytic saprotrophic Ascomycete fungi (Mayer et al, 2021). However, relationships between soil inorganic N availability, fungal composition, and SOM remain poorly understood in temperate forests spanning low to intermediate fertility.…”
Section: Introductionmentioning
confidence: 99%
“…[55,56]. Even more, the potential effects of N fertilization on the decomposition processes, e.g., via modified soil microbial communities/activities [57] and/or root exudation patterns [58], and thus, the availability of other nutrients to plants could not be quantified during this experiment-hampering the development of a comprehensive mechanistic understanding.…”
Section: Discussionmentioning
confidence: 99%